Creep rupture of smoothed and notched DD6 single crystal superalloy specimens subjected to high-temperature hot corrosion - Baishun Yang; Biao Li; Yaning Zhang (Materials & Design)
This work studies the creep rupture behaviors of both smoothed and V-notched DD6 Ni-based single crystal superalloy specimens under both air and corrosion conditions, within a stress range of 300 to 700 MPa at 950 °C. The corrosive medium used consisted of a mixed salt containing 95wt.% Na2SO4 and 5wt.% NaCl. Experimental results revealed that notched specimens exhibited a creep rupture life extended by 6–16 times compared to smoothed specimens, with the extension becoming more pronounced as the stress concentration increased. High-temperature hot corrosion (HTHC) shortened the creep rupture time by up to 40 %. A significant HTHC-creep interactive effect was found through comparative creep experiments in air and corrosion conditions. The HTHC affected the fracture modes of the specimens, with factors such as the amount of salt infiltration into the superalloy, the corrosion duration, and specimen configurations playing critical roles. Microstructural analysis revealed that, compared with γ′ precipitates, γ matrix phase was more prone to creep damage and was more susceptible to corrosion.